Natural and moral history of the Indies - Acosta, José de, 1540-1600 (Chronicles of the New World order., 2002)
The Natural and Moral History of the Indies, the classic work of New World history originally published by José de Acosta in 1590, is now available in the first new English translation to appear in several hundred years. A Spanish Jesuit, Acosta produced this account by drawing upon his own observations as a missionary in Peru and Mexico, as well as the writings of other missionaries, naturalists, and soldiers who explored the region during the sixteenth century. One of the first comprehensive investigations of the New World, Acosta's study is strikingly broad in scope. He describes the region's natural resources, flora and fauna, and terrain. He also writes in detail about the Amerindians and their religious and political practice.